Search for supersymmetry with jets, missing transverse momentum and at least one hadronically decaying [tau] lepton in proton-proton collisions at √s=7 TeV with the ATLAS detector - Aad, Georges; Anders, Gabriel; Anders, Christoph; Andrei, George Victor; Davygora, Yuriy; Dietzsch, Thorsten; Geweniger, Christoph; Hanke, Paul; Henke, Michael; Kasieczka, Gregor; Khomich, Andrei; Kluge, Eike-Erik; et al. (Physics letters, 2012)
A search for production of supersymmetric particles in final states containing jets, missing transverse momentum, and at least one hadronically decaying τ lepton is presented. The data were recorded by the ATLAS experiment in s=7 TeV proton-proton collisions at the Large Hadron Collider. No excess above the Standard Model background expectation was observed in 2.05fb−1 of data. The results are interpreted in the context of gauge mediated supersymmetry breaking models with Mmess=250 TeV, N5=3, μ>0, and Cgrav=1. The production of supersymmetric particles is excluded at 95% C.L. up to a supersymmetry breaking scale Λ=30 TeV, independent of tanβ, and up to Λ=43 TeV for large tanβ.